DEVELOPMENT OF KARUTA MEDIA TO IMPROVE EARLY READING SKILLS OF FIRST-GRADE STUDENTS - Mardiah, Mardiah; Sugiarsih, Septia; Melinda, Vannissa Aviana (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Reading ability is one of the fundamental skills that supports students' academic success, especially in the early years of primary education. However, many first-grade students still face challenges in acquiring sufficient reading proficiency. This study aims to develop an educational game-based learning media using Karuta to improve the early reading skills of first-grade primary school students. The research employed the Research and Development (RD) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The media was validated by media and content experts and tested in a one-group pretest-posttest design involving 26 students. Validation results showed that the Karuta media was highly valid, with scores of 86.6% from media experts and 97.6% from content experts. The t-test analysis indicated a significant improvement in students' early reading skills after using the media (p = 0.000 0.05). Furthermore, students gave highly positive responses (99.4%) regarding the media’s attractiveness, ease of use, and usefulness in supporting reading. These findings suggest that Karuta-based learning media is not only feasible but also effective and engaging in helping young learners develop foundational reading skills. It can serve as an innovative and interactive alternative for teachers in early grade classrooms to foster students' interest and achievement in reading.